Optimization of a sperm cryopreservation protocol for spotted wolffish (Anarhichas minor Olafsen, 1772) - Santana, João Paulo Ribeiro Proença (2019)
Spotted wolffish is a potential candidate for cold water aquaculture, presenting high growth rates in captivity, good fillet yielding and a valuable and tasty meat. Reproduction in captivity is dependent on in vitro fertilization, however, low sperm volume with relatively low cell concentration and the lack of gametes synchronization (simultaneous availability of mature eggs and sperm) represent a challenge for the aquaculture industry. In this context, it is crucial the development of protocols, such as sperm cryopreservation, that allow sperm storage and maximization of its use. Sperm was diluted in a solution described by Kime and Tveiten (2002), and four sequential experiments were conducted. First, three different cryoprotectants (DMSO; 1, 2-propanediol; and methanol) at different concentrations (5, 10, and 20%) were tested for their toxicity. Second, sperm was cryopreserved in 0.5ml straws, at different distances from the liquid nitrogen (1.5, 2.5, 4.5, and 7.5cm) that correspond to different freezing rates. Afterwards, two different thawing rates (1min at 5ºC; and 25s at 10ºC) were tested. Finally, the fertilization capacity of cryopreserved sperm was tested against fresh, and cryopreserved and then washed sperm. The ratio of eggs with normal cell divisions, abnormal divisions or undeveloped were counted at the two-cell division stage. The trial on cryoprotectants toxicity revealed no differences between the control samples and cryoprotectants at concentration up to DMSO 10%, 1, 2-propanediol 10%, and methanol 20%, thus, these were chosen to use on the freezing trial. Motility values after freezing decreased for all the cryoprotectants, however, methanol revealed to have the lowest protective capacity and DMSO the highest throughout all the freezing rates, while propanediol presented the best results when freeze at 4.5 cm from liquid nitrogen. The thawing trial was carried using only DMSO 10% and 1, 2-propanediol 10%, revealing slight differences between the two temperatures. However, the best results were obtained using DMSO 10%. For the fertilization trial we selected the aforementioned cryoprotectant and thawing at 5ºC for 1min. Cryopreserved sperm showed lower fertilization capacity at a concentration of 5x104 spz/egg compared with fresh sperm. Nevertheless, at a concentration of 5x105 spz/egg, similar fertilizations rates to the fresh sperm were obtained. There was no improvement in the fertilization rates after washing the sperm to remove the cryoprotectant. An over dosage of DMSO revealed minor effects in abnormal divisions and lower number of developed eggs. To cryopreserve spotted wolffish sperm it is recommended that sperm is diluted on the extender described by Kime and Tveiten (2002), containing 10% DMSO, loaded on 0.5ml straws, freeze at a height of 4.5 or 7.5cm from liquid nitrogen for 10min and thawed for 1min at 5ºC. To obtain fertilization ratios equivalent to those obtained with fresh sperm, in vitro fertilization should be performed with a concentration of 5x105 cryopreserved sperm cells per egg. DMSO did not affect the eggs in the tested conditions during the contact time of 4 hours.